2009
DOI: 10.1128/aem.00198-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flagella in Virulence of the Coral Pathogen Vibrio coralliilyticus

Abstract: A recently available transposition system was utilized to isolate a nonmotile mutant of the coral-bleaching pathogen Vibrio coralliilyticus. The mutation was localized to the fhlA gene, and the mutant lacked flagella. The flhA mutant was unable to exhibit chemotaxis toward coral mucus or to adhere to corals and subsequently cause infection.Coral reefs have been described as the rain forests of the sea due to their enormous biodiversity. Unfortunately, during the past few decades nearly 30% of the worldwide cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Although chemokinesis has been observed in a range of bacteria (Barbara and Mitchell, 2003;Seymour et al, 2010), neither its disproportionate contribution to a bacterium's ability to climb chemical gradients nor its potential importance in an infection process have been previously reported. This observation indicates that chemokinesis is a powerful behavioral adaptation in V. coralliilyticus's response to host-derived chemical signals and that bacterial infection of corals may be driven by considerably more specific adaptations than a binary presence or absence of motility (Meron et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although chemokinesis has been observed in a range of bacteria (Barbara and Mitchell, 2003;Seymour et al, 2010), neither its disproportionate contribution to a bacterium's ability to climb chemical gradients nor its potential importance in an infection process have been previously reported. This observation indicates that chemokinesis is a powerful behavioral adaptation in V. coralliilyticus's response to host-derived chemical signals and that bacterial infection of corals may be driven by considerably more specific adaptations than a binary presence or absence of motility (Meron et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
“…This prevalence, together with the presence of strong chemical gradients that can extend over 2 mm from the coral surface (Kü hl et al, 1995;Mass et al, 2010), suggests that motile responses to chemical cues may be a pervasive mechanism for coral pathogens to locate and colonize their hosts. Yet, beyond evidence that motility and chemotaxis are involved in Vibrioinduced bleaching (Banin et al, 2001;Meron et al, 2009), there has been no direct, real-time observation of the motile behavior of pathogens, nor any insight into the specific chemical triggers of chemotaxis or its dependence on the host's physiological state. By integrating microfluidic experiments with the collection of coral exudates, we found that V. coralliilyticus (Pollock et al, 2010) markedly changes its motility behavior in response to the mucus of its host, Pocillopora damicornis, to rapidly target the source of the cue.…”
Section: Introductionmentioning
confidence: 99%
“…V. vulnificus (Lee et al, 2004), V. anguillarum (Ormonde et al, 2000) and V. fischeri (Millikan and Ruby, 2004), all display attenuated infection in motility-deficient mutants. Similarly, nonmotile Vc450 mutants are unable to infect the coral, Pocillopora damicornis (Meron et al, 2009). Vc450 and VcP1 contain two adjacent regions involved in lateral flagella gene system (VIC_004722-VIC_004762); however, no gene products were present in the proteome and no lateral flagella were observed by electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The marine environment is a heterogeneous landscape at the microscale and a bacterium's ability to accurately navigate gradients of nutrients and infochemicals may provide it with a competitive advantage (Taylor and Stocker 2012). Chemotaxis is found governing bacteria − phytoplankton interactions (Bell and Mitchell 1972;Blackburn et al, 1998;Stocker and Seymour 2012), facilitating symbioses such as that between Vibrio fischeri and squid (Mandel et al, 2012), implicated in the onset of disease (Otoole et al, 1996;Banin et al, 2001;Rosenberg and Falkovitz 2004;Larsen et al, 2004;Meron et al, 2009) and common throughout coral reefs (Tout et al, 2015b). Within this framework, reef-building corals are becoming a focal system for studying the role of motility in bacteria-host interactions in the ocean.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of temperature directly on the pathogen's host-sensing behaviors are unknown. Although warmer temperatures might increase the chance of infection in several ways, such as increasing bacterial growth rates or virulence (Kimes et al, 2012), the effect of temperature on pathogen motility appears particularly important because all putative bacterial pathogens of corals that have been identified thus far are motile (Garren et al, 2014), with both motility and increased seawater temperatures independently implicated in the infection process (Banin et al, 2001;Meron et al, 2009).…”
Section: Introductionmentioning
confidence: 99%